Understanding the different dimensions of human dignity: Analysis of the decision of the Constitutional Courth of the Republic of Slovenia on the "Tito street" case - Petra Kleindienst (DANUBE: Law, Economics and Social Issues Review, 2017)
In 2011, the Constitutional Court of the Republic of Slovenia made a historical decision on the "Tito street" case, thereby placing human dignity at the centre of the constitutional order. A few years later, some related doubts not resolved by the Constitutional Court remain. For instance, the Court argues that an exhaustive a priori definition of human dignity is impossible since the notion depends on the development of its historical and ethical substance over time. The question thus arises of why legislation states that human dignity is universal even though it can be perceived as being a product of time and place. In this paper, we strive to answer this question by arguing that human dignity has two dimensions, initial dignity and realised dignity, and interpret the Court's decision from a new angle. Thereby, the aim of this paper is to build a conceptual framework of human dignity and discuss it from a fresh perspective as well as to prove its applicability by presenting Slovenian constitutional case law. The paper offers significant insights into the discussion and may therefore help to improve future interpretations of human dignity in the field of constitutional case law.
Keywords: 330; Human Dignity; Human Rights; Constitution of the Republic of Slovenia; ConstitutionalCourt; Case Law; Democracy